Pathological findings in the endometrium after microwave endometrial ablation - Nakayama, Kentaro; Razia, Sultana; Ishibashi, Tomoka; Ishikawa, Masako; Yamashita, Hitomi; Nakamura, Kohei; Sawada, Kiyoka; Yoshimura, Yuki; Tatsumi, Nagisa; Kurose, Sonomi; Minamoto, Toshiko; Iida, Kouji; et al. (Scientific reports, 2020)
The acceptance of MEA in Japan is well demand due to its outstanding effectiveness and safety. Infrequently, a repeat MEA or hysterectomy is needed for recurrent menorrhagia in case of failure ablation. The reasons of recurrent menorrhagia subsequent MEA treatment are unclear. The objective of current study is to identify the possible causes of menorrhagia repetition following MEA, together with the observation of histological changes in the endometrium due to this treatment compared with normal cycling endometrial tissue. A total of 170 patients, 8 (4.7%) of them carried out hysterectomy after 16.8 months (range, 2–29 months) of MEA treatment. Normal (n = 47) and MEA (n = 8) treated paraffin embedded endometrial tissue were prepared for hematoxylin and eosin (H&E) and immunostaining study to recognize the histological changes in the endometrium as a result of MEA treatment. The histological features observed increased tubal metaplasia (TM) including negative expression of the estrogen receptor (ER) and progesterone receptor (PR) in the endometrium subsequent MEA treatment. Increased TM together with the absence of ER and PR expression might be a reasonable explanation for repetition menorrhagia in cases of failure ablation. Further study is required to clarify the molecular mechanisms of tubal metaplasia and the expression loss of hormone receptor in the endometrium as a result of MEA treatment. Current studies propose that low dose estrogen-progestin may not be effective with recurrent menorrhagia patient’s due to the inadequacy of hormone receptor expression in the endometrium following MEA.